Miniaturization of Broadband Right-Handed Circular Polarized (RHCP) Antenna Using 8 x 8 Square Loop Metasurfaces (MS) - Bakar, H. A.; Abd. Aziz, M. Z. A.; Ahmad, B. H.; Hassan, N.; Sulaiman, H. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In this paper, an analysis of metasurfaces (MS) structure to a right-handed circular polarized (RHCP) antenna with L-probe technique is proposed in order to miniaturize the antenna size and investigate the MS effects towards antenna performance. Firstly, the RHCP antenna was designed based on inverted suspended rectangular patch with rectangular slot and two dual notches with an air gap between substrate and copper plate layer at distance of 10 mm. Next, the MS is placed on a top layer of RHCP antenna with an air gap separation of 3 mm. The design and simulation process is done by using Computer Simulation Technology (CST) Microwave Studio Suite software. Target application for this antenna design is for Wireless Local Area Network (WLAN) which operating frequency at 2.4 GHz. Antenna performances in term of return loss, resonant frequency, bandwidth, gain, directivity, axial ratio and radiation pattern at 2.4 GHz frequency are analyzed. The comparison result of simulation and measurement show that the proposed RHCP antenna without MS (Design A) and with MS (Design B) obtained bandwidth more than 200 MHz and forming miniaturize of RHCP antenna with substrate size reduction up to 39.5 %, yet achieving a similar antenna performance.